KPC and VIM producing Enterobacter cloacae strain from a hospital in northeastern Venezuela - Martínez, Dianny; Marcano, Daniel; Salgado, Nurys; Cuaical, Nirvia; Rodriguez, Lucy; Caña, Luisa; Medina, Belkis; Guzman, Militza; De Donato, Marcos (Investigación Clínica, 2015)
An 83-year-old male patient is admitted to the central hospital in Cumaná, Venezuela with severe urinary infection, history of hospitalizations and prolonged antimicrobial treatments. A strain of Enterobacter cloacae was isolated showing resistance to multiple types of antibiotics (onlysensitive to gentamicin), with phenotype of serine- and metallocarbapenemases. Both, blaVIM-2 and bla genes were detected in the isolate. This is the first report of an Enterobacteriaceae species producing both KPC carbapenemase and VIM metallo carbapenemase in Venezuela. This finding has a great clinical and epidemiological impact in the region, because of the feasibility of transferring these genes, through mobile elements to other KPC strains of Enterobacter and to other infection-causing species of bacteria.